2003
DOI: 10.1023/a:1025489313497
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We report a case of a recurrent empty follicle syndrome. The patient was admitted to our intracytoplasmic injection program because of her partner's azoospermia. Ovarian stimulation was accomplished using gonadotrophin therapy after treatment with oral contraceptive pills followed by gonadotrophin-releasing hormone agonist. Thirty-six hours after the administration of HCG (human chorionic gonadotrophins), transvaginal oocyte retrieval yielded no oocytes despite the aspiration and flushing of all available foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Decleer et al reported a greater number of excellent oocytes and cryopreserved embryos after dual triggering, compared with hCG only [ 28 ]. A recent paper recommended prolonging the time interval between ovulation triggering with a GnRHa and oocyte pick-up to overcome any existing impairment in granulosa cell function, oocyte meiotic maturation, or cumulus expansion for patients with abnormal follicular maturation [ 29 ]. We did not evaluate the effects of a dual trigger on oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…Decleer et al reported a greater number of excellent oocytes and cryopreserved embryos after dual triggering, compared with hCG only [ 28 ]. A recent paper recommended prolonging the time interval between ovulation triggering with a GnRHa and oocyte pick-up to overcome any existing impairment in granulosa cell function, oocyte meiotic maturation, or cumulus expansion for patients with abnormal follicular maturation [ 29 ]. We did not evaluate the effects of a dual trigger on oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…Uygur et al [42] suggested prolonging the interval between ovulation triggering and OPU. However, the strategy regarding prolonging the interval between triggering and OPU has little evidence to be generally recommended.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…In the study of Zreik et al, they reported that the incidence of EFS was 1.8% and the recurrence rate was 24% in 34–39-year-old patients and 57% in women over 40 years of age [ 29 ]. Early follicular atresia or apoptosis was first mentioned by Uygur et al as the cause of EFS [ 30 ]. Vutyavanich et al obtained immature oocytes from the filtrate of IVF follicular fluid in a case of EFS [ 31 ].…”
Section: Types Of Omasmentioning
confidence: 99%